Crash and Tell : Stories - Baker, Lori, 1962- (Book collections on Project MUSE., 2011)
In Crash & Tell, Lori Baker plays with a variety of narrative voices and styles, skillfully treading the line between traditional storytelling and the literary avant-garde. The collection provides a unique account of womenAEs lives, exploring the dark side of romance, workplaces laced with the surreal, and familiar neighborhoods made strange through the lens of memory and murder. The stories range from the comical re-imagining of Jane GoodallAEs life among the apesù told from the eyes of Jane as a debutante escapeeùto a professional research subject who outwits a cunning psychiatrist. In other st.